The Role of Social Adjustment in a Collegiate Behavioral Activation Program. Issue 5 (September 2022) - Felton, Julia W.; Triemstra, Justin D.; Reynolds, Elizabeth K.; Hale, Nicole; Magidson, Jessica F.; Lejuez, Carl W.
The transition to college is associated with significant changes in social support networks and concomitant increases in depressive symptoms. First-year students who are more socially engaged within their new academic settings may experience greater overall wellbeing. Behavioral activation (BA) is an evidence-based intervention which promotes individuals' engagement with valued activities and has been examined as a possible primary prevention for depressive symptoms among first-year students. Yet, the important role of social adjustment, and its impact on students' activity level, has not yet been considered. The current study is a secondary data analysis of research evaluating a BA-based intervention embedded into a first-year orientation course. The aim of the project was to evaluate the efficacy of BA on improving social adjustment and the effect of social adjustment on subsequent depressive symptoms. A diverse sample of college students ( n  = 71) attending a state university in the mid-Atlantic region reported on their levels of depression, behavioral activation, and social adjustment. Students then received either BA or standard programming. Results suggest that improved engagement in valued activities at mid-intervention was associated with increases in students' perceptions of their own social adjustment. This, in turn, predicted steeper decreases in rates of depressive symptoms post-intervention. Findings also indicate that greater social adjustment improved the efficacy of a BA-based intervention in reducing depressive symptoms, but had no impact on depressive symptoms for students receiving the standard orientation programming.